The Impact of Instant Coffee and Decaffeinated Coffee on the Gut Microbiota and Depression-Like Behaviors of Sleep-Deprived Rats - Gu, Xinyi; Zhang, Shuyi; Ma, Weini; Wang, Qixue; Li, Ying; Xia, Chenyi; Xu, Ying; Zhang, Ting; Yang, Li; Zhou, Mingmei (Frontiers in Microbiology, 2022)
Objective: Based on our previous research, chronic paradoxical sleep deprivation (PSD) can cause depression-like behaviors and microbial changes in gut microbiota. Coffee, as the world’s most popular drink for lack of sleep, is beneficial to health and attention, and can eliminate cognitive sequelae caused by poor sleep. The purpose of this study is to investigate the effects of coffee and decaffeinated coffee on paradoxical sleep deprivation (PSD) rats. Research design and methods: A total of 32 rats were divided into 4 groups: control group, PSD model group, conventional coffee group, and decaffeinated coffee group. Behavioral tests, including sucrose preference test, open field test, forced swimming test and tail suspension test, as well as biochemical detection for inflammatory and anti-oxidant indexes were performed. Effects of coffee and decaffeinated coffee on gut microbiota of PSD rats were investigated by 16S rRNA gene sequencing. Results: Coffee and decaffeinated coffee significantly improved the depression-like behaviors. Moreover, the serum levels of IL-6 and TNF-α were decreased in both coffee and decaffeinated coffee group, as well as the levels of SOD and GSH-Px were increased. Gut microbiota analysis revealed that the abundance of S24-7, Lachnospiraceae, Oscillospira and Parabacteroides were significantly increased in PSD rats, while the abundance of Akkermansia and Klebsiella were significantly decreased. After the treatment of coffee and decaffeinated coffee, the abundance of above gut microbiota was all restored in different degrees. Coffee had relatively more significant effects on PSD induced depressive-like behaviors, while the difference between coffee and decaffeinated coffee was not obvious in correcting the disorder gut microbiota. Conclusions: These findings have shown that both coffee and decaffeinated coffee is effective for sleep deprivation-induced depression-like behaviors and dysbiosis of gut microbiota, and indicated that caffeine may be not the only key substance of coffee for regulating gut microbiota.